DEMOLITION- THE NEED OF THE DEAD BUILDINGS - Kumar, Anup; Arora, Akshay (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Demolition- The need of the dead buildings. This idea basically deals with the demolition of the structure with the help of various techniques that are being used currently for the demolition of the structure. Every civil engineer designs a building for a life period upto which that building can properly work. After that the existence of a structure is very dangerous. Hence removal of such structures with proper safety measures has got great importance. Demolition of a building means tearing down or falling down of a building with the help of heavy equipments or explosives. These techniques have been used widely for the structures which are aged and are not favorable for the future use. We are basically deals with the floor-by-floor demolition of the building. our basic aim is how a demolition work is to be performed safely and also elaborate different steps involved before and during the execution of a demolition job. The various steps involved before the demolition process includes surveying, removal of reuse materials, and preparation of demolition plan, stability data and the precautionary safety measures to be taken for the further demolition process. The presence of aged buildings which lack proper care and maintenance poses potential threats to human society and the community at large.